2021
DOI: 10.5999/aps.2020.01648
|View full text |Cite
|
Sign up to set email alerts
|

Cephalic lateral crural advancement flap

Abstract: Background In lower lateral cartilage (LLC) surgery, cephalic trimming poses risks for the collapse of the internal and external nasal valves, pinched nose, and drooping deformity. The cephalic lateral crural advancement (CLCA) technique presented herein was aimed at using a flap to increase nasal tip rotation and support the lateral crus, in addition to the internal and external nasal valves, by avoiding grafts without performing excision.<br/>Methods This study included 32 patients (18 female and 14 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
(28 reference statements)
0
5
0
Order By: Relevance
“…25,34,50,52,58,60,66 Significant improvement in ROE, nasal patency scores, SCHNO-S-C/O, NOSE, and VAS-F/C was seen following the sandwich technique described by Öztürk, as well as the mini-LCSG, LCSG, cephalic lateral crural advancement (CLCA) flap, LCO technique, cephalic turn-in flap, and superior-based sliding flap technique with complete cartilage preservation. 25,50,52,58,60,66 Significant improvement was also seen in SCHNOS-O/C scores following a subdorsal septal approach encompassing all three preservation techniques. 34 Abdelwahab et al found a significant improvement in both SCHNOS-C and VAS-C (p < 0.05) for all lateral crural preservation techniques in cosmetic rhinoplasty.…”
Section: Group 3: Lateral Crural Preservation Componentmentioning
confidence: 99%
See 3 more Smart Citations
“…25,34,50,52,58,60,66 Significant improvement in ROE, nasal patency scores, SCHNO-S-C/O, NOSE, and VAS-F/C was seen following the sandwich technique described by Öztürk, as well as the mini-LCSG, LCSG, cephalic lateral crural advancement (CLCA) flap, LCO technique, cephalic turn-in flap, and superior-based sliding flap technique with complete cartilage preservation. 25,50,52,58,60,66 Significant improvement was also seen in SCHNOS-O/C scores following a subdorsal septal approach encompassing all three preservation techniques. 34 Abdelwahab et al found a significant improvement in both SCHNOS-C and VAS-C (p < 0.05) for all lateral crural preservation techniques in cosmetic rhinoplasty.…”
Section: Group 3: Lateral Crural Preservation Componentmentioning
confidence: 99%
“…58,66 Similarly, Öztürk and Bulutboth demonstrated a significant improvement in ROE score at 12 months following either the sandwich technique or CLCA flap. 52,60 Improvement in SCHNOS-O score was seen only in combined cosmetic and functional rhinoplasty with mini-LCSG, although there was an improvement in nasal patency Likert scale scores or VAS-F following both the sandwich technique and CLCA flap. 52,60,66 The remaining references included in this group focus on subjective outcomes, complication rates, and revisions rates with no statistically significant data available.…”
Section: Group 3: Lateral Crural Preservation Componentmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, some flaps have been described based on use of cartilage in the cephalic trim area. O'Halloran 8 described “lateral crural J flap,” Janis et al 9 described “lower lateral crural turnover flap,” Ozmen et al 10 described “sliding alar cartilage flap,” Apaydın 11 described “lateral crural turn-in flap,” Sazgar 12 described “lateral crural hinged flap,” Bohluli et al 13 described “lateral crural suspension flap,” Ashtiani et al 14 described “lateral crural transposition flap,” Kuran et al 15 described “lateral crural rein flap,” Tas 16 described “superior-based transposition flap” and Bulut 17 described “cephalic lateral crural advancement flap.” The focus of all these defined flaps is on the lower third of the nose, such as obtaining stronger lower lateral cartilages, supporting the nasal valves, controlling tip rotation. In all of these studies, flaps were designed symmetrically and bilaterally.…”
mentioning
confidence: 99%